How Does A Translator Deal with the Word â€˜Sh*Tâ€™? - Aida, Nurul; Kristianto, Bayu (Universitas Serambi Mekkah, 2020)
This paper is a small part of my thesis aiming to investigate the translation strategies applied by a translator in translating the taboo word â€œsh*tâ€. Taboo words are one of the language featuresrequiring a careful analysis as their message is generally different from their literal meaning. This isa descriptive translation study (DTS) using a book entitled â€œThe Subtle Art of Not Giving a F*ckâ€(2016) as ST and its Indonesia translation as TT. The data selected were the taboo word â€œsh*tâ€ andits derivation (shit/shitty/bullshit/bullshitty/shithead/shitheap/ batshit/shit-ton). The data wereanalyzed qualitatively by grouping them based on their functions. Then, ST and TT were compared toexamine the translation strategies applied by the translator. The theory used was McEnery (2006) toexplore the taboo word functions and that of Newmark (1988), Baker (2011) and Davoodi (2009) to examine the translation strategies. The results show that the word â€œsh*tâ€ functions as a predicative negative adjective, emphatic intensifier, idioms, literal, imagery, and pronominal form. The strategiesmostly applied in a predicative negative adjective, emphatic intensifier, idioms, imagery, andpronominal functions is the paraphrase strategy. Meanwhile, the strategies applied in the literalfunction are omission and taboo to taboo. This research reveals that the translator attempted to avoidthe occurrence of the taboo word â€œsh*tâ€ and its derivation in his translation by mostly applying theparaphrase strategy. Future research is suggested to explore the translatorâ€™s motives behind thestrategy selection.Keywords: taboo word sh*t, taboo word function, translation strategies.